45. Pułk Strzelców Kresowych w obronie Tomaszowa Mazowieckiego we wrześniu 1939 r. - Jarno, Witold (Przegląd Nauk Historycznych, 2012)
The article describes the 45 Infantry Regiment fighting in defense of Tomaszów Mazowiecki in September 1939. The regiment was part of the 13th Infantry Division, fighting in the composition of the Army „Prussia”. This Division was given the task to defend the region Tomaszów Mazowiecki and stop German XVI Panzer Corps. Fighting on the left wing defence of the Division, the 45 Infantry Regiment (commanded by Colonel Stanislaw Hojnowski) given the task of defending Tomaszow Mazowiecki. After a day-long battle German tanks broke the Polish defenses and conquered the northern part of the city. In this situation the regiment was ordered to withdraw to the north. During the march through the streets of Tomaszów, the regiment was strafed by German troops and saboteurs. In a few hours a night battle, the regiment was broken up and no longer be an organized unit. During the fighting killed more than 100 soldiers, including the commander of the regiment, Colonel Hojnowski. Survivors soldiers retreated to-wards Inwłodza, where he joined the own division and participated in the following battles. Fear in defense Tomaszow permanently etched in the history of the regiment, and is still remembered by the people of the city.